(untitled) (Jurnal Arsitektur ARCADE, 2026)
Biophilic design integrates natural elements into the built environment with the aim of improving occupant well-being and psychological recovery quality. In the context of hospital buildings, this approach holds relevance given the strong and well-documented relationship between the physical environment and the patient recovery process. However, studies in Indonesia and Southeast Asia have tended to examine biophilic design and energy efficiency as two separate research domains. This study identifies and analyses the application of biophilic design principles in two reference hospitals in Singapore, namely the National Heart Centre Singapore (NHCS) and Khoo Teck Puat Hospital (KTPH), using a qualitative descriptive approach through a case study method. Data were collected through secondary document analysis and cross-referencing with precedent studies. The findings indicate that both hospitals apply several biophilic design principles from the fourteen-pattern framework developed by Browning, Ryan, and Clancy (2014), including visual connection with nature, dynamic and diffuse lighting, thermal and airflow variability, material connection with nature, and prospect. The analysis demonstrates that these principles not only support the therapeutic quality of the environment but also contribute to passive energy efficiency strategies. This study concludes that an integrated approach to biophilic design can simultaneously address the need for a healing environment and building energy performance, particularly in the tropical climate context of Southeast Asia.